Speech Recognition in Noise in Single-Sided Deaf Cochlear Implant Children on Using Adaptive Digital Microphone Technology - Speck, I.; Müller, T.; Jakob, T. F.; Wiebe, K.; Aschendorff, A.; Arndt, S.; Wesarg, T.; Hassepass, F. (Journal of the American Academy of Audiology, 2020)
Background Previous research demonstrated benefits of adaptive digital microphone technologies (ADMTs) in adults with single-sided deafness (SSD) having a cochlear implant (CI). Children with SSD are especially affected by background noise because of their noise exposure in kindergarten and school.Purpose This article aims to evaluate possible effects of ADMT on speech recognition in background noise in children with SSD who use a CI.Study Sample Ten children between 5 and 11 years of age were included.Data Collection and Analysis Speech recognition in noise was assessed for one frontal distant and two lateral speakers. The speech stimulus was presented at a speech level of 65 dB(A) and noise at a level of 55 dB(A). For the presentation condition with one frontal speaker, four listening conditions were assessed: (1) normal-hearing (NH) ear and CI turned off; (2) NH ear and CI; (3) NH ear and CI with ADMT; and (4) NH ear with ADMT and CI. Listening conditions (2) to (4) were also tested for each lateral speaker. The frontal speaker was positioned directly in front of the participant, whereas the lateral speakers were positioned at angles of 90 degrees and –90 degrees to the participant's head.Results Children with SSD who use a CI significantly benefit from the application of ADMT in speech recognition in noise for frontal distant and for lateral speakers. Speech recognition improved significantly with ADMT at the CI and the NH ears.Conclusion Application of ADMT significantly improves speech recognition in noise in children with SSD who use a CI and can therefore be highly recommended. The decision of whether to apply ADMT at the CI NH ear or bilaterally should be made for each child individually.
Keywords: cochlear implant; single-sided deafness; speech recognition in noise; remote wireless microphone system; children; pediatric